Clinical comparison of at-home and in-office dental bleaching procedures: A randomized trial of a split-mouth design - Machado, Lucas Silveira; Anchieta, Rodolfo Bruniera; dos Santos, Paulo Henrique [UNESP]; Briso, André Luiz Fraga [UNESP]; Tovar, Nick; Janal, Malvin N.; Coelho, Paulo Guilherme; Sundfeld, Renato Herman [UNESP] (Quintessence Publishing, 2016)
The objective of this split-mouth clinical study was to compare a combination of in-office and at-home dental bleaching with at-home bleaching alone. Two applications of inoffice bleaching were performed, with one appointment per week, using 38% hydrogen peroxide. At-home bleaching was performed with or without in-office bleaching using 10% carbamide peroxide in a custom-made tray every night for 2 weeks. The factor studied was the bleaching technique on two levels: Technique 1 (in-office bleaching combined with home bleaching) and Technique 2 (home bleaching only). The response variables were color change, dental sensitivity, morphology, and surface roughness. The maxillary right and left hemiarches of the participants were submitted to in-office placebo treatment and in-office bleaching, respectively (Phase 1), and at-home bleaching (Phase 2) treatment was performed on both hemiarches, characterizing a split-mouth design. Enamel surface changes and roughness were analyzed with scanning electron microscopy (SEM) and optical interferometry (IFM) using epoxy replicas. No statistically significant differences were observed between the bleaching techniques for either the visual or the digital analyses. There was a significant difference in dental sensitivity when both dental bleaching techniques were used, with in-office bleaching producing the highest levels of dental sensitivity after the baseline. Microscopic analysis of the morphology and roughness of the enamel surface showed no significant changes between the bleaching techniques. The two techniques produced similar results in color change, and the combination technique produced the highest levels of sensitivity. Neither technique promoted changes in morphology or surface roughness of enamel.